2022
DOI: 10.3389/fphar.2021.781282
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Fibroblast Migration and Proliferation Upon Wounding or Lipopolysaccharide Exposure is Mediated by Stathmin

Abstract: The dermal fibroblast is a crucial executor involved in wound healing, and lipopolysaccharide is a key factor in initiating the migration and proliferation of the dermal fibroblasts, followed by wound healing. However, the underlying molecular mechanism is still unknown. In this study, we demonstrated that stathmin increased concomitantly with p38/MAPK pathway activation by lipopolysaccharide stimulation of the human dermal fibroblast (HDF), which induced microtubule (MT) depolymerization followed by increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Thus, it is important to also consider the biocompatibility toward dermal fibroblast cells, the main cell type present in this layer . In addition, dermal fibroblasts also play a significant role in wound healing, where they proliferate and migrate to form granulation tissue to repair the wound . Hence, testing on dermal fibroblasts is essential to ensure safety during sampling in the dermal layer or a wound.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to also consider the biocompatibility toward dermal fibroblast cells, the main cell type present in this layer . In addition, dermal fibroblasts also play a significant role in wound healing, where they proliferate and migrate to form granulation tissue to repair the wound . Hence, testing on dermal fibroblasts is essential to ensure safety during sampling in the dermal layer or a wound.…”
Section: Results and Discussionmentioning
confidence: 99%
“…56 In addition, dermal fibroblasts also play a significant role in wound healing, where they proliferate and migrate to form granulation tissue to repair the wound. 57 Hence, testing on dermal fibroblasts is essential to ensure safety during sampling in the dermal layer or a wound. Similar framework tests with HaCaT were adopted, where the viability of HFF for different cell incubation times and cell seeding densities were studied followed by the proliferation for 48 h. Figure 3a shows the HFF viability after 24 and 48 h incubation in HD and LD seeding.…”
Section: Hff Viability and Proliferationmentioning
confidence: 99%
“…Not only that, MPB-BA also showed significantly enhanced cell migration after 24 h and 48 h treatment, compared to the Ctrl group. As we know, enhanced fibroblast migration is crucial for wound healing, which is closely related to tissue repair and regeneration 45,52,53) . Our results suggested that MPB-BA owned the favorable ability to induce fibroblast migration, so as to promote periodontal soft tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is a pathological feature of most chronic inflammatory diseases, whereby fibroblast proliferation and migration lead to the excessive deposition of fibrous connective tissue, reducing its functionality [39]. LPS activates fibrosis, modulating the release of inflammatory cytokines and increasing fibroblast proliferation and migration [40], [41]. Results showed that the expression of the pro-inflammatory genes TNF-α, transforming growth factor beta (TGF-β), interleukin (IL)-1 and IL-6 increased significantly 24 h after LPS stimulation of fibroblasts.…”
Section: Modulation Of Pro-fibrotic Genes and Inhibition Of Fibroblas...mentioning
confidence: 99%